1982
DOI: 10.1111/j.1469-8137.1982.tb03376.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Six Species of Vesicular‐arbuscular Mycorrhizal Fungi and Their Effects on Soybean at Four Soil Temperatures

Abstract: SUMMARYThe effects of four soil temperatures on colonization of soybean roots, sporulation and enhancement of plant growth by six species of vesicular-arbuscular (VA) mycorrhizal fungi were tested. The mean values for all fungus and plant variates in three tests were generally greatest at 30 °C and lowest at 18 °C. Four fungus species, Glomus claroideum, Glomus datum, Gigaspora pellucida, and Gigaspora gregaria, produced the greatest number of spores per gramme of colonized root at 24 °C, while Glomus mosseae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 10 publications
5
50
1
1
Order By: Relevance
“…In particular, it has been shown that AM fungi usually increase flower amount, the number of flowering plants in a stand, or flowering earliness (Schenck and Smith 1982;Gaur et al 2000;Scagel 2004;Perner et al 2007;Bunn et al 2009;Asrar et al 2012;Bona et al 2015). However, it also has been found that AM fungi can have no effects on flowering (Linderman and Davis 2004), delay its onset, or increase its duration (Schenck and Smith 1982;Dubský and Vosátka 2000;Saia et al 2014a;Jin et al 2015). Such effects could depend on both the competition for N and photosynthates between AM fungi and flowers (Johnson et al 1982) and the ability of AM fungi to reduce nutrient deficiency or other stresses for the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that AM fungi usually increase flower amount, the number of flowering plants in a stand, or flowering earliness (Schenck and Smith 1982;Gaur et al 2000;Scagel 2004;Perner et al 2007;Bunn et al 2009;Asrar et al 2012;Bona et al 2015). However, it also has been found that AM fungi can have no effects on flowering (Linderman and Davis 2004), delay its onset, or increase its duration (Schenck and Smith 1982;Dubský and Vosátka 2000;Saia et al 2014a;Jin et al 2015). Such effects could depend on both the competition for N and photosynthates between AM fungi and flowers (Johnson et al 1982) and the ability of AM fungi to reduce nutrient deficiency or other stresses for the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…Myorrhizal symbiosis may affect plant reproduction also without affecting vegetative parameters (Schenck & Smith, 1982;Pendleton, 2000;Philip et al ., 2001). It is possible that these effects are mediated by hormones since hormone levels are altered in mycorrhizal plants (Ludwig-Müller, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of efficacy have been made with unknown quantities of inoculum (Mosse, 1975;Powell, 1979;Menge et al, 1980;Bagyaraj & Sreeramulu, 1982;Poweil, Clark & Verberne, 1982) or inoculum concentrations based upon spore numbers (Carling, Brown & Brown, 1979;Schenck & Smith, 1982). However, the spore numbers in inoculum often have been poorly correlated with the percent of VAM-roots in the inoculated plants (Daft & Nicolson, 1969;Daniels, McCool & Menge, 1981;Smith, 1981).…”
Section: Introductionmentioning
confidence: 99%